2013
DOI: 10.1042/bst20120272
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B transmission and possible new roles for extracellular vesicles

Abstract: Coxsackievirus B1, a member of the Picornaviridae family is a non-enveloped single-stranded RNA virus associated with human diseases including myocarditis and pancreatitis. Infection of the intestinal mucosa, lined by polarized epithelial cells, requires interaction of coxsackievirus with apically located DAF (decay-accelerating factor) before transport to the basolaterally located CAR (coxsackie and adenovirus receptor), where entry is mediated by endocytosis. As with many other non-enveloped viruses, coxsack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Macropinocytosis is morphologically defined by the presence of membranous extensions of outwardly polymerizing actin termed membrane ruffles. It has been identified as an entry mechanism for several pathogens, including B2 adenovirus (Kalin et al, 2010), Coxsackie B virus (Inal and Jorfi, 2013), influenza A virus (de Vries et al, 2011), Ebola virus (Aleksandrowicz et al, 2011), Vaccinia virus (Rizopoulos et al, 2015), Nipah virus (Vogt et al, 2005), Kaposi's Sarcoma-Associated Herpesvirus (Raghu et al, 2009), and Newcastle disease virus (Tan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Macropinocytosis is morphologically defined by the presence of membranous extensions of outwardly polymerizing actin termed membrane ruffles. It has been identified as an entry mechanism for several pathogens, including B2 adenovirus (Kalin et al, 2010), Coxsackie B virus (Inal and Jorfi, 2013), influenza A virus (de Vries et al, 2011), Ebola virus (Aleksandrowicz et al, 2011), Vaccinia virus (Rizopoulos et al, 2015), Nipah virus (Vogt et al, 2005), Kaposi's Sarcoma-Associated Herpesvirus (Raghu et al, 2009), and Newcastle disease virus (Tan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because exit via EMVs provide a non-cytolytic method for CVB escape, this mechanism could potentially prolong viral replication in the host cell. EMVs could also enhance viral stability in the extracellular space as well as mask the virus from host neutralizing antibodies (Inal & Jorfi, 2013) (Masciopinto, Giovani et al, 2004). Though intact virions were observed in EMVs observed under electron microscopy (Robinson, Tsueng et al, 2014), these structures could presumably contain free viral RNA and still remain infectious.…”
Section: Introductionmentioning
confidence: 99%
“…For instance SV40 was detected in intra-cytoplasmic smooth membrane vesicles and described as being released from the cell before cytopathic effects are seen [18]. Similarly, cocksackie B3 virus was found to be transferred from cell to cell through microvesicles [19]. We also recently reported that in the case of non-enveloped lytic parvoviruses that progeny virions are actively transported from the nucleus to the plasma membrane (PM) through vesicles in a gelsolin-dependent manner [20].…”
Section: Introductionmentioning
confidence: 99%